Parámetros para la selección de talentos en las etapas formativas y su incidencia para integrar el equipo de Liga Deportiva Universitaria de Loja profesional en las escuelas de futbol de Liga Deportiva Universitaria de Loja 2013 - Cumbicus Quevedo, José Anibal (2015)
The selection of talents requires of towering levels of preparation which can be given starting from an appropriate planning and execution of the acquired knowledge, this allows to solve different situations that show up in the trainings or competitions. The topic that you work was “parameters for the selection of talents in the formative stages and its incidence to integrate the team of Liga Deportiva Universitaria of professional Loja in the schools of soccer of Liga Deportiva Universitaria of Loja 2013”. What I take myself to work the following problem: as it impacts the selection of talents in formative stages to integrate the team of Liga Deportiva Universitaria of Loja professional in the schools of soccer of Liga Deportiva Universitaria of Loja. The investigation has as general objective; to analyze the parameters for the selection of talents in the formative stages and its incidence to integrate the team of Liga Deportiva Universitaria of professional Loja in the schools of soccer of League Sport University student of Loja. And specific objectives as, to determine if the use of parameters is the appropriate one to obtain a good seleccionamiento of talents on the part of the trainers of the club Liga Deportiva Universitaria of Loja he/she Ties to know if the trainers of the club have a good seleccionamiento of players to project them to the team of first category, to apply new parameters for the selection of talents in the formative divisions of the club Liga Deportiva Universitaria of Loja Ties. The prosecutions used for the hypothesis confirmation were the scientific, deductive method. Inductive; and for the elaboration of the analysis one went to the descriptive method. The techniques that were applied were through instruments like the survey to the trainers and the test to the players of the club Liga Deportiva Universitaria of Loja it Ties, what allowed me to end up checking the work hypotheses. The main results to those that were approached in this investigation refer to the selection of talents and to measure the grade of the trainer’s knowledge for the professional formation of the players and their incidence